Conversor CA-CC Ćuk baseado na célula de comutação de três estados com correção de fator de potência aplicado em carregador de banco de baterias - Pacheco, Juliano de Oliveira (2014)
This work presents the study and implementation of an ac-dc Ćuk converter based on the three state switching cells applied in charger stations for electric vehicles. This converter has, as main characteristics, reduction of conducting power losses in the semiconductors, a single stage topology and current source behavior for both input and output terminals. As drawbacks, the topology presents: the voltage across the semiconductors is equal to the sum of the input and the output voltages, and a difference between the current values through the semiconductors caused by an inappropriate layout of the power prototypes or by a lack of symmetry between the control signals. The analysis of the converter is made through the qualitative and quantitative studies, beyond the analysis of the semiconductor losses which are presented as well. The current and voltage of the battery are controlled by the average current mode technique, which consist in a fast current control loop if compared with the terminals battery voltage control loop. The topology is design for 1 kW output power, 220 V in input voltage and 162 V in the output terminals (12 batteries in series connection). Experimental results for resistive load, as well batteries, are shown in order to verify the functionalities of the topology and its characteristics